Attitudes, knowledge, and willingness to be vaccinated against seasonal influenza among patients hospitalized with influenza-like-illness: impact of diagnostic testing. Issue 4 (2nd April 2020) - Tubiana, Sarah; Launay, Odile; Galtier, Florence; Tattevin, Pierre; Postil, Deborah; Vanhems, Philippe; Lenzi, Nezha; Verger, Pierre; Duval, Xavier
ABSTRACT: Influenza vaccine adherence remains low. Communication of virological diagnosis to adults hospitalized with influenza-like illness (ILI) could improve their willingness to be subsequently vaccinated. We prospectively assessed, in adults hospitalized with ILI in six French university hospitals, their willingness to be vaccinated against influenza in the subsequent season, both before and after the communication of RT-PCR Influenza laboratory result; we identified then the determinants associated with the willingness to be vaccinated. A total of 309 patients were included during the 2012–2013 and 2013–2014 influenza seasons; 43.8% reported being vaccinated against influenza for the current season; before communication of influenza laboratory results, 65.1% reported willingness to be vaccinated during the subsequent season. Influenza was virologically confirmed in 103 patients (33.3%). The rate of vaccine willingness increased to 70.4% ( p = .02) after communication of influenza laboratory results. Factors independently associated with the willingness to be vaccinated were the perception of influenza vaccine benefits (adjusted relative risk (aRR): 1.06, 95%CI 1.02–1.10), cues to action (aRR: 1.08, 95%CI 1.03–1.12), current season influenza vaccination (aRR: 1.38, 95%CI 1.20–1.59) and communication of a positive influenza laboratory result (aRR: 1.18, 95%CI 1.03–1.34). This last was associated with the willingness to be vaccinated only in the subpopulation of patients not vaccinated (aRR: 1.53, 95%CI 1.19–1.96). In patients hospitalized with ILI, communication of a positive influenza diagnostic led to a better appreciation of the disease's severity and increased the willingness to be vaccinated. This approach might be particularly beneficial in patients who do not have a history of influenza vaccination.